Establishment of drug-resistant HBV small-animal models by hydrodynamic injection - Junjun Cheng; Yanxing Han; Jian-Dong Jiang (Elsevier, 2014)
In antiviral therapy of hepatitis B virus (HBV) infection, drug resistance remains a huge obstacle to the long-term effectiveness of nucleoside/tide analogs (NAs). Primary resistance mutation (rtM204V) contributes to lamivudine (LAM)-resistance, and compensatory mutations (rtL180M and rtV173L) restore viral fitness and increase replication efficiency. The evaluation of new anti-viral agents against drug-resistant HBV is limited by the lack of available small-animal models. We established LAM-resistance HBV replication mice models based on clinical LAM-resistant HBV mutants. Double (rtM204V+rtL180M) or triple (rtM204V+rtL180M+rtV173L) lamivudine-resistant mutations were introduced into HBV expression vector, followed by hydrodynamic injection into tail vein of NOD/SCID mice. Viremia was detected on days 5, 9, 13 and 17 and liver HBV DNA was detected on day 17 after injection. The serum and liver HBV DNA levels in LAM-resistant model carrying triple mutations are the highest among the models. Two NAs, LAM and entecavir (ETV), were used to test the availability of the models. LAM and ETV inhibited viral replication on wild-type model. LAM was no longer effective on LAM-resistant models, but ETV retains a strong activity. Therefore, these models can be used to evaluate anti-viral agents against lamivudine-resistance, affording new opportunities to establish other drug-resistant HBV small-animal models.